Symptom Diary Use and Improved Survival for Patients With Heart Failure. (November 2017) - Park, Linda G.; Dracup, Kathleen; Whooley, Mary A.; McCulloch, Charles; Jin, Chengshi; Moser, Debra K.; Clark, Robyn A.; Pelter, Michele M.; Biddle, Martha; Howie Esquivel, Jill
Abstract : Background: Attention to symptoms of weight gain and dyspnea are central tenets of patient education in heart failure (HF). However, it is not known whether diary use improves patient outcomes. The aims of this study were to compare mortality among rural patients with HF who completed versus did not complete a daily diary of weight and symptom self-assessment and to identify predictors of diary use. Methods and Results: This is a secondary analysis of a 3-arm randomized controlled trial on HF education of self-care with 2 intervention groups versus control who were given diaries for 24 months to track daily weight, HF symptoms, and response to symptom changes. Mean age was 66±13, 58% were men, and 67% completed diaries (n=393). We formed 5 groups (no use, low, medium, high, and very high) based on the first 3 months of diary use and then analyzed time to event (cardiac mortality, all-cause mortality, and HF-related readmission) starting at 3 months. Compared with patients with no diary use, high and very high diary users were less likely to experience all-cause mortality ( P =0.02 and P =0.01, respectively). Self-reported sedentary lifestyle was associated with less diary use in an adjusted model (odds ratio, 0.66; 95% confidence interval, 0.46–0.95; P =0.03). Depression and sex were not significant predictors of diary use in the adjusted model. Conclusions: In this study of 393 rural patients with HF, we found that greater diary use was associated with longer survival. These findings suggest that greater engagement in self-care behaviors is associated with better HF outcomes. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique Identifier: NCT00415545.